2012
DOI: 10.1029/2011ja017359
|View full text |Cite
|
Sign up to set email alerts
|

Thin current sheets in the presence of a guiding magnetic field in Earth's magnetosphere

Abstract: [1] A self-consistent theory of relatively thin anisotropic current sheets (TCS) in collisionless plasma is developed, taking into account the presence of a guiding field B y (all notations are used in the GSM coordinate system). TCS configurations with a finite value of guiding field B y are often observed in Earth's magnetotail and are typical for Earth's magnetopause. A characteristic signature of such configurations is the existence of a magnetic field component along the direction of TCS current. A genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 83 publications
1
29
0
Order By: Relevance
“…Measurements in the magnetospheric current sheet show that, the larger the guide field, the lower the amplitude of the current in the sheet. This is in agreement with theoretical estimates and numerical calculations, which also demonstrate a decrease in the densities of the current and plasma and an increase in the thickness (smaller transverse dimension) of the sheet [7]. A decrease in the amplitude of the current and plasma density and an increase in the thickness of the sheet with an increase in the guide field [8][9][10], as well as the appearance of curved asymmetric plasma sheets [11,12], were detected in laboratory experi ments.…”
supporting
confidence: 91%
“…Measurements in the magnetospheric current sheet show that, the larger the guide field, the lower the amplitude of the current in the sheet. This is in agreement with theoretical estimates and numerical calculations, which also demonstrate a decrease in the densities of the current and plasma and an increase in the thickness (smaller transverse dimension) of the sheet [7]. A decrease in the amplitude of the current and plasma density and an increase in the thickness of the sheet with an increase in the guide field [8][9][10], as well as the appearance of curved asymmetric plasma sheets [11,12], were detected in laboratory experi ments.…”
supporting
confidence: 91%
“…The effect of asymmetry of particle reflection/transition in the CS with B y = 0 has been mentioned by many authors on the basis of numerical simulations (Zhu and Parks, 1993;Baek et al, 1995;Delcourt et al, 2000;Malova et al, 2012;Grigorenko et al, 2013). Here we have shown that this effect occurs due to two peculiarities of the system: (1) decrease of the probability of capture in the right well and (2) shrinking of the uncertainty curve.…”
Section: Discussionmentioning
confidence: 69%
“…Masuda et al, 2001;Schrijver, 2009). This component can affect particle acceleration (Litvinenko, 1996), CS structure (Whipple et al, 1984;Roth et al, 1996;Artemyev, 2011;Malova et al, 2012) and CS dynamics (Galeev et al, 1986;Kuznetsova and Roth, 1995;Silin and Büchner, 2003;Karimabadi et al, 2005;Artemyev and Zimovets, 2012). The influence of B y on particle motion has been studied in several papers with the help of numerical modelling of test trajectories (Karimabadi et al, 1990;Büchner and Zelenyi, 1991;Zhu and Parks, 1993;Baek et al, 1995;Chapman and Rowlands, 1998;Delcourt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Solving equation (28) = and the macroscopic expression for P zz matches the expression calculated from the v z 2 moment of the distribution function (48).…”
Section: [3])mentioning
confidence: 99%